From Ground to Grain: Tracing Phosphorus and Potassium in Flooded Rice Cultivar Grown on Histosols - Naba R. Amgain; Yuchuan Fan; Matthew T. VanWeelden; Abul Rabbany; Jehangir H. Bhadha (Agriculture, 2022)
To trace the phosphorus (P) and potassium (K) content in flooded rice (Oryza sativa L), 14 rice cultivars commonly grown in the Southern United States were evaluated for their P and K concentration in tissue and grain. Field experiments were conducted at two locations in Everglades Agriculture Area (EAA), where flooded rice was cultivated on organic Histosols. Soil pH and Mehlich-3 phosphorus (M3P) were significantly different between locations. At Site I, soil pH, M3P, and Mehlich-3 potassium (M3K) varied in the range of 6.8–7.1, 21.4–36.4 mg kg−1, and 53.9–151.0 mg kg−1, respectively. At Site II, soil pH, M3P and M3K varied in the range of 6.9–7.3, 11.2–20.5 mg kg−1, and 64.8–104.1 mg kg−1, respectively. Stem potassium was the only measured parameter that was significantly different among rice cultivars at both sites. At Site I and Site II, stem K ranged from 14.2–26.6 mg kg−1 and 10.4–19.4 mg kg−1, respectively. No significant difference in yield among cultivars was observed at Site I, whereas Site II had a significant difference in yield among cultivars. At Site I and Site II, yields ranged from 3745–7587 kg ha−1 and 2627–6406 kg ha−1, respectively. None of the cultivars ranked consistently in the same top and bottom position for each measured parameter. Total phosphorus (TP) concentration was highest in grain, whereas total potassium (TK) concentration was highest in the stem. Results suggest incorporation of rice stem into the soil could potentially add fertilizer back to the soil which helps in fertility management.